Formation of magnetite by bacteria and its application - Arakaki, Atsushi (The Royal Society, 2008)
Magnetic particles offer high technological potential since they can be conveniently collected with an external magnetic field. Magnetotactic bacteria synthesize bacterial magnetic particles (BacMPs) with well-controlled size and morphology. BacMPs are individually covered with thin organic membrane, which confers high and even dispersion in aqueous solutions compared with artificial magnetites, making them ideal biotechnological materials. Recent molecular studies including genome sequence, mutagenesis, gene expression and proteome analyses indicated a number of genes and proteins which play important roles for BacMP biomineralization. Some of the genes and proteins identified from these studies have allowed us to express functional proteins efficiently onto BacMPs, through genetic engineering, permitting the preservation of the protein activity, leading to a simple preparation of functional protein–magnetic particle complexes. They were applicable to high-sensitivity immunoassay, drug screening and cell separation. Furthermore, fully automated single nucleotide polymorphism discrimination and DNA recovery systems have been developed to use these functionalized BacMPs. The nano-sized fine magnetic particles offer vast potential in new nano-techniques.